1990
DOI: 10.2214/ajr.154.3.2106225
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging in patients with intractable complex partial epileptic seizures.

Abstract: Detailed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
2
40
0
2
Order By: Relevance
“…65 A further five studies reported incorrectly localised scans, ranging from 2 to 7%. 33,41,56,106,115 Three used site of surgery as the reference standard, 33,56,115 and the remaining two a combination of tests. 41,106 The observed heterogeneity in the localisation categories could not be explained by variation in reference standard used, weighting of scan (T1 or T2), slice orientation, number of patients, patient spectrum (adults and/or children), proportion of male to female, year of publication (a surrogate for improved technology) or the subgroup investigated.…”
Section: Results Of the Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…65 A further five studies reported incorrectly localised scans, ranging from 2 to 7%. 33,41,56,106,115 Three used site of surgery as the reference standard, 33,56,115 and the remaining two a combination of tests. 41,106 The observed heterogeneity in the localisation categories could not be explained by variation in reference standard used, weighting of scan (T1 or T2), slice orientation, number of patients, patient spectrum (adults and/or children), proportion of male to female, year of publication (a surrogate for improved technology) or the subgroup investigated.…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…Test for heterogeneity: I 41 Venz, 1994 110 Zhou, 1994 30,33,46,54,77 For the purpose of further analysis, these studies were considered to have included patients with both temporal and nontemporal lobe epilepsy as we assumed that they would have made it clear if they had been restricted to patients with a particular type of epilepsy. Only two studies included an appropriate patient spectrum.…”
Section: Figure 10 Unclear Timing Spect: Proportion Of Scans In Each mentioning
confidence: 99%
See 3 more Smart Citations